2016
DOI: 10.1016/j.adolescence.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

How fair is my world? Development of just world beliefs among Kenyan students

Abstract: This study is a cross‐sectional analysis of Kenyan adolescents' beliefs in a just world (BJW). Prior research suggests that BJW declines across adolescence and differentiate between Personal and General BJW. However, little research has been conducted in African samples or developing economies. Adolescents from three schools in Western Kenya (n = 1960) completed the questionnaires to understand how their Personal and General BJW differed across grades, and between schools, tribes, and sexes. Contrary to prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Such belief enables people to confront the physical and social environment as stable and orderly. Although BJW was considered to be a personality disposition and unlikely to change over time ( Correia et al, 2009 ; Faccenda and Pantaleon, 2011 ), many studies indicated that it was less stable in adolescence ( Oppenheimer, 2005 ; Peter and Dalbert, 2010 ; Barreiro, 2013 ) and could be affected by educational environment ( Dalbert, 2001 ; Dalbert and Stoeber, 2006 ; Thomas and Mucherah, 2016 ). For example, a longitudinal study found that adolescents’ personal BJW significantly increased over a period of 5 to 8 months; moreover, after controlling for age and gender, both school climate and family climate had an impact on the personal BJW ( Dalbert and Stoeber, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such belief enables people to confront the physical and social environment as stable and orderly. Although BJW was considered to be a personality disposition and unlikely to change over time ( Correia et al, 2009 ; Faccenda and Pantaleon, 2011 ), many studies indicated that it was less stable in adolescence ( Oppenheimer, 2005 ; Peter and Dalbert, 2010 ; Barreiro, 2013 ) and could be affected by educational environment ( Dalbert, 2001 ; Dalbert and Stoeber, 2006 ; Thomas and Mucherah, 2016 ). For example, a longitudinal study found that adolescents’ personal BJW significantly increased over a period of 5 to 8 months; moreover, after controlling for age and gender, both school climate and family climate had an impact on the personal BJW ( Dalbert and Stoeber, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Turkish/Muslim males evaluated their personal life as more just than Turkish/Muslim females did. In line with Thomas and Mucherah's (2016) Kenya study, this difference could be interpreted as a result of gender inequality that they experienced in the Turkish society or it may be because of that immigrant females face more difficulties and risks in their personal life. Future studies looking into these differences are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, based on the studies mentioned above, we argued that the function of BJW would differ among advantaged and disadvantaged students and we expected that the assimilation function should be stronger for the Turkish students compared to their German peers. As in the studies of Thomas and Mucherah (2016) and Thomas and Napolitano (2017) just world research shows that BJW and justice cognitions might be associated with students' demographics such as gender, age, and school type which they attend. For example, Correia and Dalbert (2007) found that female students tended to evaluate their teachers as more just than male students.…”
Section: The Buffer Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…Lerner (1980) first described the belief in a just world (BJW) as the belief that the world is a fair place where people get what they deserve and determine their own fate. Research has shown important differences between BJW groups based on their level of privilege in experimental studies (Laurin, Fitzsimons, & Kay, 2011; Thomas & Mucherah, 2016), yet no studies of this nature have been conducted in Latin American, the global region with the most inequality (Barcena & Byanyima, 2016). In addition, little work seeking to understand justice beliefs across status groups has been conducted on adolescent samples.…”
Section: Introductionmentioning
confidence: 99%